태화강 내 연어(Oncorhynchus keta) 치어의 방류에 따른 성장 모니터링 - 허준욱; 윤지우; 임한규; Hur, Jun Wook; Yoon, Ji Woo; Lim, Han Kyu (한국해양생명과학회지, 2021)
To secure basic data by monitoring the growth of salmon (Oncorhynchus keta) released to the Taehwa River. After discharge, the characteristics of the young salmon distribution and migration rate habitat were investigated for two years. A total of 4 points [Sunbawi bridge (St.1), Guyeong bridge (St.2), Samho bridge (St.3), and Myeongchon bridge (St.4)] were investigated. The survey of 2017 indicating an increase of 10 mm in average length and 0.8 g in average weight, and the survey of 2018 indicating an increase of 10 mm in average length and 0.5 g in average weight. Among 39 species, 10 insectivorous and 12 omnivorous, are believed to compete with young salmon for food. 6, 5, 6 and 8 predatory fish species has emerged at each site, respectively. According to this study, it is believed that St.1 and St.2 points are more proper as discharge location of young salmon because these two points have less varied in depth, flow rate, salt concentration etc. In addition, it is thought that the night or dawn time in early January is the best discharge time of young salmon fish because predatory fish such as Korean piscivorous chub and bass etc. does not eat food actively at that time. 태화강에서 방류한 연어(Oncorhynchus keta) 치어의 성장, 생존 및 어류상 등의 모니터링를 통한 생태학적 기초 자료를 확보하고자, 방류 후 연어 치어의 지점별 포획개체수, 성장 및 어류상 특성을 조사하였다. 태화강 상류로부터 총 4개 지점[선바위교(St.1), 구영교(St.2), 삼호교(St.3), 명촌대교(St.4)]에서 2년간 조사를 실시하였다. 2017년 연어 치어 방류 후 전장은 평균 10 mm, 체중은 평균 0.8 g의 증가를 나타내었다. 2018년 연어 치어 방류 후 평균 전장 10 mm, 체중 0.5 g의 증가를 나타내었다. 연어 치어를 포식할 수 있는 어식성 어류는 St.1에서 6종(동사리, 숭어, 배스, 꺽지, 황어 및 끄리), St.2에서 5종(동사리, 황어, 배스, 꺽지 및 끄리), St.3에서 6종(큰가시고기, 가물치, 날망둑, 배스, 황어, 끄리) 및 St.4는 8종(큰가시고기, 베도라치, 문절망둑, 날망둑, 풀망둑, 강준치, 점농어 및 황어)이 출현하였다. 본 연구결과 연어 치어는 체중의 증가보다 전장 및 체장의 성장에 집중하는 것으로 나타났다. 또한, 적정 방류지역은 포식생물의 서식이 적고 수심, 유속, 염분 등의 변화가 적은 St.1과 St.2 지점이 적절할 것으로 판단되며 방류 시기는 끄리 및 배스 등의 포식어류의 먹이활동이 활발하지 않은 1월 초순 혹은 포식 활동이 적은 야간이나 새벽시간에 방류하는 것이 적절할 것으로 판단된다.